2010
DOI: 10.1517/14712590903530633
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of switching adalimumab from a prefilled syringe to an autoinjection pen

Abstract: This study provides further evidence to support the use of the autoinjection pen as a delivery option for adalimumab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 17 publications
(10 reference statements)
0
48
0
Order By: Relevance
“…For instance, RA patients administering methotrexate with an AI experience less pain and prefer it over the PFS [21,22]. Selfinjection by AI is also preferred by patients using adalimumab [23,24], etanercept [25][26][27], and golimumab [28,29], as well as in other disease areas, such as diabetes and growth hormone deficiency [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, RA patients administering methotrexate with an AI experience less pain and prefer it over the PFS [21,22]. Selfinjection by AI is also preferred by patients using adalimumab [23,24], etanercept [25][26][27], and golimumab [28,29], as well as in other disease areas, such as diabetes and growth hormone deficiency [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Several commercial subcutaneous products up to 1 mL are available, including Enbrel (Amgen, Thousand Oaks, CA), Humira (AbbVie, North Chicago, IL), Simponi (Janssen Biotech, Horsham, PA), and Stelaris (Janssen Biotech). [5][6][7][8][9] When the therapeutic dose can be formulated in 1 mL, prefilled syringes and autoinjectors typically serve as the preferred delivery systems for subcutaneous selfadministration. 6,10 To limit the injection volume to 1 mL, monoclonal antibody formulations often need to be formulated at high concentrations at !100 mg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] When the therapeutic dose can be formulated in 1 mL, prefilled syringes and autoinjectors typically serve as the preferred delivery systems for subcutaneous selfadministration. 6,10 To limit the injection volume to 1 mL, monoclonal antibody formulations often need to be formulated at high concentrations at !100 mg/mL. High-concentration liquid monoclonal antibody formulations can present problems in manufacturing and delivery because of high viscosities, limitations of protein solubility, aggregation, and protein stability under long-term storage.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of other bDMARDs have been approved and are now commercially available; many of these treatments are administered by subcutaneous (SC) injection, with a number of presentations and devices currently being available (prefilled syringes, vial and syringe, and autoinjector devices). A number of studies have reported that patients with RA prefer autoinjector devices over conventional methods of treatment administration, with patients citing such factors as these devices being easier to use, more convenient, more acceptable, less painful, and less time-consuming [57]. …”
Section: Introductionmentioning
confidence: 99%